Zakaria Ouzon’s Thought on Hadith - Muhammad Rikza Muqtada (UIN Sunan Kalijaga Yogyakarta, 2017)
Departing from the discomfort over the stagnation of intellectual life in Muslim world today, which mainly imprisoned in ”traditional reading” (qirā’ah taqlīdiyyah), Zakaria Ouzon tries to break the tradition by restoring religious texts into historical frame. For him, the ultimate authority of revelation belongs only to the Qur’an, while other religious texts are the products of ijtihād and very open to criticism and more dynamic. Hadith and its sciences are very dynamic. Therefore, Ouzon looks at the hadits from different frame. For him, the hadits is the Prophet’s reports on events that happened to the Prophet and his interaction with his companions. As the logical consequence, Ouzon offers the hadith criticism models with an emphasis on the historicity and rationality of the content. The knowledge of hadith not only limited to the past as the truth was improsined within the text, but it is necessary to contextualize the hadith. Therefore, the hadith sciences is very dependent on the dynamics of social and humanities sciences along with scientific knowledge, so that the truth that is brought also becomes local and temporal entity.[Berangkat dari kegelisahan atas fenomena kejumudan nalar umat Islam saat ini yang terbiasa dengan pembacaan tradisional (qirā’ah taqlīdiyyah), Zakaria Ouzon berusaha mendobrak tradisi dengan mengembalikan teks-teks agama pada sisi historisitasnya. Baginya, yang memiliki otoritas kewahyuan hanyalah al-Qur’an, sementara teks-teks agama lainnya bersifat ijtihādī sehingga ia sangat terbuka atas kritik dan lebih dinamis. Hadis dan Ilmu Hadis merupakan wilayah yang sangat dinamis. Karena itu Ouzon memandang Hadis dari episteme yang berbeda. Baginya, Hadis merupakan laporan-laporan sahabat Nabi atas peristiwa yang terjadi pada diri Nabi dan interaksinya dengan sahabat-sahabatnya. Konsekuensi logisnya, Ouzon menawarkan model-model kritik hadis dengan penekanan pada sisi historisitas dan rasionalitas teks. Pengetahuan hadis tidak sekedar pengetahuan masa lalu dengan atribut kebenarannya ada pada teks, tetapi upaya kontekstualisasi hadis adalah keharusan pengetahuan. Karena itu pengetahuan hadis sangat bergantung pada dinamika pengetahuan sosial humaniora dan pengetahuan sains modern sehingga kebenaran yang diusung juga bersifat lokal dan temporal.]